Immunotherapy-associated autoimmune hemolytic anemia - Uqba Khan; Tarik Hadid; Farman Ali; Muhammad Siddique Khurram; Awais Zaka (Journal for ImmunoTherapy of Cancer)
Background Immunotherapy has been widely used in the treatment of several solid and hematologic malignancies. Checkpoint inhibitors have been the forefront of cancer immunotherapy in recent years. Cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed cell death 1 (PD-1) pathway are the prototypic checkpoint targets for immunotherapy. When combined, CTLA-4 and PD-1 checkpoint inhibitors work synergistically, but with increased probability of toxicity. The following case represents an unusual adverse effect of combined treatment with ipilimumab and nivolumab used for treatment of metastatic melanoma.Case presentation A 43-year-old woman with metastatic melanoma presented with severe generalized weakness and fatigue. She has received two cycles of ipilimumab and nivolumab, last administered 3 weeks prior to her presentation. Initial investigations revealed severe anemia with appropriate reticulocytosis, severely elevated lactate dehydrogenase, undetectable haptoglobin level and positive direct coombs test. Patient was diagnosed with severe autoimmune hemolytic anemia secondary to ipilimumab and nivolumab. She was successfully treated with high dose steroids and rituximab.Conclusions In our case, we present a rare but serious adverse effect of immunotherapy. We illustrate the clinical presentation and management of immunotherapy associated autoimmune hemolytic anemia. Immunotherapy has revolutionized the treatment of many malignant conditions; therefore, it is imperative for health care professionals caring for cancer patient to be familiar with the adverse effects of immunotherapy, which allow for early recognition and management of these potentially lethal side effects.